(untitled) (Journal for Studies in Humanities and Social Sciences, 2019)
This article interrogates the undercurrents of small states foreign policy and the determinants of foreign policy making in small states. It question small states are positioned in the web of international relations with other player, such as large states. The research is guided by the assumption that small states are somewhat limited by domestic and external factor, which are the driving catalysts of international relations agendas. The analysis aims to determine how the smallness of a state can be a challenge, and how small states can survive the limitations of their smallness. The article makes use of Liberalism/Neo-Liberalism theories of International Relations (IR) Studies.